Strategies to Increase Sales of Micro, Small and Medium Enterprises by Utilizing the Tik Tok Shop in an Islamic Perspective - Finik Kharianti; Zuhrinal M Nawawi (Penerbit Jurnal Indonesia, 2022)
This study aims to find out what strategies make the TikTok platform an effective media promotion in marketing a product and increasing sales to micro, small and medium enterprises. In this research the method used is a descriptive approach, this research is a research that collects data contained in social media, be it books, journals and so on. From this research, the data used are primary and secondary data. The results showed that sales promotion by giving discounts or price reductions, giving vouchers and coupons, free goods (gif), product guarantees and free shipping. Publicity with a direct approach to consumers. Interactive marketing by involving consumers in sales activities. TikTok with various interesting features in it. These things help micro, small and medium enterprises to market their products and increase their sales. So optimal utilization of TikTok features and a good approach with consumers, can help in increasing sales. Thus TikTok becomes an effective promotional medium in marketing activities.